Dari Ngak-Ngik-Ngok, ke Cengeng, lalu Ambyar: Politik Afektif Musik Indonesia - Fauzanafi, Muhammad Zamzam (Universitas Padjadjaran, 2024)
This article examines the relationship between music and politics through the lens of affective resonance, spanning the Soekarno era (ngak-ngik-ngok), the New Order (cengeng), and the Reformation (ambyar) era. Using music analysis and remote ethnography as its methods, the article argues that music, particularly its sonic qualities, plays a crucial role in shaping affective politics—a form of politics distinct from ideological politics. The banning of ngak-ngik-ngok music during the Soekarno era was not merely an anti-imperialism or anti-colonialism ideological stance but also an exercise in affective politics, where Soekarno sought to regulate citizens'